2001
DOI: 10.1073/pnas.191223098
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the quorum-sensing protein LuxS reveals a catalytic metal site

Abstract: The ability of bacteria to regulate gene expression in response to changes in cell density is termed quorum sensing. This behavior involves the synthesis and recognition of extracellular, hormonelike compounds known as autoinducers. Here we report the structure of an autoinducer synthase, LuxS from Bacillus subtilis, at 1.6-Å resolution (Rfree ‫؍‬ 0.204; Rwork ‫؍‬ 0.174). LuxS is a homodimeric enzyme with a novel fold that incorporates two identical tetrahedral metal-binding sites. This metal center is compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 52 publications
4
93
2
1
Order By: Relevance
“…It shared 88% identity with its closest luxS relative from Vibrio parahaemolyticus 16 (accession number ZP_05120871) at the aa level, although no significant similarity was found between luxS 72 and that of V. parahaemolyticus 16 at the nucleotide level, indicating high divergence of DNA sequence of luxS 72 . Alignment of luxS 72 to that of several other Vibrio species indicated that the variance of aa largely occurred in the C-terminus of the protein and luxS 72 has all the conserved aa identified in Hilgers and Ludwig (2001) Figure S2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It shared 88% identity with its closest luxS relative from Vibrio parahaemolyticus 16 (accession number ZP_05120871) at the aa level, although no significant similarity was found between luxS 72 and that of V. parahaemolyticus 16 at the nucleotide level, indicating high divergence of DNA sequence of luxS 72 . Alignment of luxS 72 to that of several other Vibrio species indicated that the variance of aa largely occurred in the C-terminus of the protein and luxS 72 has all the conserved aa identified in Hilgers and Ludwig (2001) Figure S2). …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the novel luxS cluster obtained in this study might be involved in the same pathway as that of V. harveyi or V. cholerae. The LuxS 72 aa sequence has all of the uniformly conserved residues for other S-ribosylhomocysteinases, including those implicated in metal binding (Hilgers and Ludwig, 2001). It is therefore not surprising that this protein can function to drive synthesis of AI-2 when expressed in E. coli DH5a.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] All LuxS proteins are homodimers. Each subunit is a single polypeptide chain which share a novel α-β fold consisting of four-stranded antiparallel β-sheet bordered by 3 α helices on one side and a short 3 10 helix on the other side.…”
Section: S-ribosylhomocysteinase (Luxs)mentioning
confidence: 99%
“…Each subunit is a single polypeptide chain which share a novel α-β fold consisting of four-stranded antiparallel β-sheet bordered by 3 α helices on one side and a short 3 10 helix on the other side. [46][47][48] The LuxS sequence alignment from 26 species, revealed 23 repeated amino acid residues, some of which are part of the active center. In the crystal, as well as in solution, LuxS is present as symmetric homodimer with two symmetric active sites.…”
Section: S-ribosylhomocysteinase (Luxs)mentioning
confidence: 99%
See 1 more Smart Citation